Study of sickle cell anaemia with clinical and hematological correlation - M., Vasundhara; R., Ramdas; A., Bhagya Lakshmi; S., Satish Kumar; R., Subash (International Journal of Research in Medical Sciences, 2016)
Background: Sickle cell anaemia is a hemoglobinopathy with the production of abnormal hemoglobin, HbS which when exposed to hypoxemia produces sickling of RBC. Severity of the disease depends on the percentage of HbS. Rise in the levels of Hb F is associated with less intense clinical course. Drugs targeted at increasing levels of HbF have prognostic significance. The aim of the study is to analyse the age, sex distribution, clinical, hematological and electrophoretic appearances and to compare with other studies. Methods: 300 sickle cell positive patients, both male and females who attended OPD were studied with all the clinical findings and hematological parameters. 52 cases were subjected to electrophoresis. Results: Males were 154 and females were 146. Degree of anaemia was severe in females when compared to males. Of 52 cases subjected for electrophoresis 36 were homozygous, 15 were heterozygous and 1 case Sickle thalassemia. 7 cases showed HbF above 5%. Conclusions: Most of the patients were under 40 yrs suggesting decreased survival after that age. An increased level of HbF was associated with better prognosis suggesting the need to target at drugs which increase HbF.